Healthy Communities Initiative: a preliminary assessment of the University of Missouri-Sedalia health promotion partnership. Issue 1 (1st January 2016) - Majee, Wilson; Goodman, Laurel; Vetter-Smith, Molly; Canfield, Shannon
Abstract: The persistence and growth of health disparities among different population groups have heightened interest in understanding the unique role University–community partnerships can play in promoting health and well-being. Through a qualitative approach, this study used in-depth interviews to understand the conditions and factors that determine the effectiveness of collaborative University–community partnerships, and how collective action can impact members and their communities. Findings show that the success of a partnership stems from the community's social protective factors such as community capacity to participate in collaborative projects, sense of community, community participation, and community extent of empowerment fostered by the collective process. The study concludes with a call for committed collaboration between partnership members and among community coalitions.